Spoils system is not dead : the development and effectiveness of the merit system in Western Balkans - Stančetić, Veran (Array, 2020)
The paper analyses the development of the merit system and its effectiveness in the administrations of the Western Balkan countries. First, the development of the merit concept is described; its origin and genesis, as well as the positive effects it has had mostly in Western democracies. However, the basic hypothesis presented in the paper is that in most Western Balkan countries, the spoils system still remains a reality, even though the law stipulates the merit system. This hypothesis is demonstrated through practical evidence, as well as by comparing the merit system in the Western Balkans with that of Western democracies, in both a formal and a practical sense. The paper also analyses the negative consequences of this situation, as well as the benefits that the citizens would have in a merit system. In addition, solutions are offered, i.e., a model of reform that would overcome the existing situation.